2022
DOI: 10.1111/dme.14921
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and food literacy among young Canadian adults living with type 1 diabetes

Abstract: Aim Nutrition and food literacy encompasses knowledge, skills and confidence to prepare healthy meals. This project aimed to assess and compare the proportion of young Canadian adults (18–29 years old) living with type 1 diabetes and without diabetes (controls) who demonstrated adequate nutritional health literacy. Methods This cross‐sectional study involved participants completing an online survey that included questions on socio‐economic status, nutrition knowledge, confidence and skills in meal preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…We found overall moderate food skills, 60-79 % was considered as moderate. Our findings are consistent with a previous study that measured aspects of food skills in Canadian adults (mean age 22•5 years, n 191), in which half (47•6 %) of the participants prepared meals themselves (33) . Whether participants in our study were responsible for their own food shopping was included to represent the food skills competencies of food literacy 'having food budgeting skills' by Slater et al (4) Although we acknowledge that other tools may have been more suitable to measure food skills in youth, we did not include a fully validated tool to limit the participant burden.…”
Section: Food Skillssupporting
confidence: 92%
“…We found overall moderate food skills, 60-79 % was considered as moderate. Our findings are consistent with a previous study that measured aspects of food skills in Canadian adults (mean age 22•5 years, n 191), in which half (47•6 %) of the participants prepared meals themselves (33) . Whether participants in our study were responsible for their own food shopping was included to represent the food skills competencies of food literacy 'having food budgeting skills' by Slater et al (4) Although we acknowledge that other tools may have been more suitable to measure food skills in youth, we did not include a fully validated tool to limit the participant burden.…”
Section: Food Skillssupporting
confidence: 92%
“…Second, the diet of most patients is in uenced by their families, and they may give up treatment at any time. Studies have shown [21] that among patients with higher nutritional literacy, independent food preparation is a promoting factor. Therefore, patients should be encouraged to prepare meals independently.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted among Turkish adults showed that the score based on the SFLQ is moderately correlated with the TSOY-32 score and weakly correlated with the Newest Vital Sign test [ 21 ]. Other studies showed that the SFLQ score was significantly associated with purchasing behaviors among consumers [ 23 ] and with skills and confidence in preparing meals in young adults suffering from type 1 diabetes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their analysis showed that the SFLQ score was significantly associated with purchasing behaviors, gender, and the place of residence. Recently, Itzkovitz et al observed a significant relationship between the SFLQ score and higher cooking skills and confidence in preparing healthy meals among young Canadian adults living with type 1 diabetes [ 24 ].…”
Section: Introductionmentioning
confidence: 99%